Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS dengan Menggunakan Metode Problem Solving di Kelas V Sekolah Dasar - Karim, Recca Augtiyenda; Zuardi, Zuardi; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the students achievement in learning social science used Problem Solving of 5th grade elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were students of 5th grade were 30 people consist of 12 men and 18 women. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 75% and the cycles II of 92,86% b) Implementation teacher’s activity of I cycle was 73,43% and II cycle was 93,75% while implementation students activity of I cycle was 73,43% and II cycle was 90,62% c) the students learning outcomes in the I cycle was 77,72 and II cycle was 86,92. It can be concluded that used Problem Solving method can improve students achievement in learning social science of 5th grade at SDN 09 ATB Kota Padang.Keyword : Learning outcomes, Social science, Problem Solving